Posttraumatic stress and posttraumatic growth and their relationship to coping and self-efficacy in Northwest Australian cyclone communities - Pooley, J.; Cohen, L.; O'Connor, Moira; Taylor, M. (2013)
The main focus of disaster research conducted to date has been on providing insights into the negative consequences of experiencing a serious threat or adversity. The present study extends this research endeavor by investigating the positive posttrauma resiliency experiences of 512 survey respondents living in four cyclone-prone communities in Northwest Australia. The findings reveal that disaster stress is often accompanied by disaster growth and, thus, provides an alternative resilience-based way of viewing postdisaster interventions. (PsycINFO Database Record © 2013 APA, all rights reserved).